The viral marketing ( Its orgins, understandable, his campaing (stages, measured - انيس, غانم رزوقي (Journal of Economics and Administrative Sciences, 2014)
The concept of viral marketing is a modern concepts in the field of marketing studies and research in marketing functions, by relying on the notion of the spoken word and the written word, it is worth mentioning the lack of local research on viral marketing, research, analysis, and application and significantly encouraged interest in this topic by addressing basic concepts stand on its first seeds with focus theoretically on the viral marketing campaign planning across a field research adoption questionnaire prepared for this purpose had been distributed to a sample on a random sample of students of the Business Administration Department / College of administration and economics / University of Baghdad of 56 students and using the adequate statistical tools to analyze these data depending upon using the ( spss ) program.One of the most important results of the research the information sent over the Internet sites of interest and credibility can be used positively a relationship between the viral marketing concept and the proliferation of advertising messages via websites.